2013
DOI: 10.1002/2013jg002384
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedbacks between phosphorus deposition and forest canopy trapping, evidence from Southern Mexico

Abstract: [1] For some phosphorus (P)-limited ecosystems, vegetation can be sustained by atmospheric P inputs. The ability of the canopy to trap airborne particles influences atmospheric P deposition. This dependence suggests a positive feedback, which could impact forest regeneration following deforestation. We examine how the amount of P deposited atmospherically varies as a function of forest canopy characteristics. We quantify the amount of P in bulk deposition (i.e., rainfall and dry deposition) and throughfall fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 66 publications
0
19
0
4
Order By: Relevance
“…Our annualized rates of throughfall organic C (Table ; 94.46 ± 10.39 and 63.31 ± 15.43 kg C ha −1 a −1 , including and excluding T1, respectively) are in the middle of the range of values found across numerous rural studies (range: 29–161 kg C ha −1 a −1 : Michalzik et al, ; Schmidt et al, ; Pitman et al, ; Fujii et al, ; Arisci et al, ), but to our knowledge, no study reports organic C in throughfall in cities around the world. Annualized rates of throughfall total P (5.21 ± 0.79 and 2.60 ± 0.67 kg P ha −1 a −1 , including and excluding T1, respectively, 93–94% inorganic P; Table ) are elevated compared to throughfall rates found in nonurban studies (range 0.34–2.7 kg P ha −1 a −1 : Kopáček et al, ; Parron et al, ; Coble & Hart, ; Runyan et al, ; Lequy et al, ; Du et al, ; Salehi et al, ), but as with organic C, we did not find any past urban studies measuring P in throughfall worldwide. Taken as a whole, these results suggest that atmospheric deposition can be an important nonpoint source of organic N, organic C, and total P during the growing season in urban areas.…”
Section: Resultsmentioning
confidence: 94%
“…Our annualized rates of throughfall organic C (Table ; 94.46 ± 10.39 and 63.31 ± 15.43 kg C ha −1 a −1 , including and excluding T1, respectively) are in the middle of the range of values found across numerous rural studies (range: 29–161 kg C ha −1 a −1 : Michalzik et al, ; Schmidt et al, ; Pitman et al, ; Fujii et al, ; Arisci et al, ), but to our knowledge, no study reports organic C in throughfall in cities around the world. Annualized rates of throughfall total P (5.21 ± 0.79 and 2.60 ± 0.67 kg P ha −1 a −1 , including and excluding T1, respectively, 93–94% inorganic P; Table ) are elevated compared to throughfall rates found in nonurban studies (range 0.34–2.7 kg P ha −1 a −1 : Kopáček et al, ; Parron et al, ; Coble & Hart, ; Runyan et al, ; Lequy et al, ; Du et al, ; Salehi et al, ), but as with organic C, we did not find any past urban studies measuring P in throughfall worldwide. Taken as a whole, these results suggest that atmospheric deposition can be an important nonpoint source of organic N, organic C, and total P during the growing season in urban areas.…”
Section: Resultsmentioning
confidence: 94%
“…During the study, P T input was 138 g/ha from bulk precipitation, and 180 and 178 g/ha from throughfall in the mature and secondary forest stands, respectively. Annually, P T input was 590 g/ha from bulk precipitation, and 810 and 1920 g/ha from throughfall in the secondary and mature forest stands [ Runyan et al , ]. Annual stemflow P inputs in the secondary forest were 65 g P/ha, while they were 58 g P/ha in the mature forest [ Das , ].…”
Section: Resultsmentioning
confidence: 99%
“…Rain water was sampled as part of a long‐term study investigating atmospheric P deposition to these forest stands beginning in 2006 [ Das et al , ; Runyan , ; Runyan et al , ]. Five collectors (10 L plastic collectors with openings 515 cm 2 in size, placed 0.6 m above the ground, and covered with 0.5 mm nylon mesh screen to exclude debris) were deployed during March 2010 [ Runyan et al , ]. Sample collection was coordinated with two local assistants and occurred immediately following each precipitation event to minimize losses to evaporation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an empirical study has shown that the local‐scale availability of P can modulate atmospheric P deposition through a positive feedback loop involving vegetation growth (Runyan et al. ). Since small‐scale lateral nutrient fluxes can lead to ecosystem‐level emerging properties even under stable conditions (Gravel et al.…”
Section: Implications Of the Ltnoi Processmentioning
confidence: 99%